Pengaruh Disiplin Kerja dan Motivasi Terhadap Kinerja Pegawai Pengadilan Negeri Karawang Kelas 1b - Widya Sri Hartati; Suroso; Syifa Pramudita Faddila (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to examine the influence of work discipline and motivation on performance. This research uses quantitative methodology through a verification approach, a sample of 75 people from Class 1B Karawang District Court employees. Correlation test results with a sig value of 0.001 < 0.05. So it can be concluded that there is a correlation between the independent variable work discipline and the dependent variable performance. Correlation test results with a sig value of 0.001 < 0.05. It can be concluded that motivation has a positive and significant effect on performance. The calculated F calculation results are 93.290 > Ftable 3.12, and the sig value is 0.001 < 0.05, so Ho is rejected. Based on these two test results, there is a simultaneous influence between work discipline and motivation variables on performance of 72.2%, the remaining 27.8% is influenced by other variables not measured in this research